Implementasi Website Untuk Meningkatkan Pelayanan Pada Kelurahan - Buhori Muslim (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
Along with the rapid progress information technology in every lifer aspect in utility advance technology especcialy to Agung Lawangan village chief as like in given information still doing as manual and needed a delivery information web principle. Methode system develop use is engineering web with the stoge : Costumer Comunication, planning, modeling, contruction and Deployment. The purpose from the website in village chief Agung Lawangan. Produce get dynamic website and easy to update every where. Beside that this website also can be one of medium in Agung Lawangan village chief to preface alternatif media easier to studing for society.